Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

4x²y + 3y²z - 2xy² - 3x²y + 4y²z

Sagot :

Answer:

=x2y−2xy2+7y2z

Step-by-step explanation:

Simplify

Let's simplify step-by-step.

4x2y+3y2z−2xy2−3x2y+4y2z

=4x2y+3y2z+−2xy2+−3x2y+4y2z

Combine Like Terms:

=4x2y+3y2z+−2xy2+−3x2y+4y2z

=(4x2y+−3x2y)+(−2xy2)+(3y2z+4y2z)

=x2y+−2xy2+7y2z

Answer:

=x2y−2xy2+7y2z